Surficial geology of a portion of Bristol, Norfolk and Plymouth Counties, Massachusetts - Stephen B Mabee; Fernandez, M. (geologic Map, 2004)
Interim digital compilation of the published surficial geology of the Assawompsett Pond, Blue Hills, Bridgewater, Brockton, Duxbury, Hanover, Scituate, Norwood, Taunton, and Whitman 7.5' quadrangles. This will be superseded by the publication of USGS OFR 2006-1260-H
Keywords: #MGSPub; #SurficialMaps; Abington; Acushnet; Avon; Boston; Braintree; Bridgewater; Brockton; Canton; Dedham; Dover; Duxbury; East Bridgewater; Easton; Foxborough; Freetown; Halifax; Hanover; Hanson; Holbrook; Kingston; Lakeville; Marshfield; Middleborough; Milton; Norwell; Norwood; Pembroke; Plympton; Quincy; Randolph; Raynham; Rochester; Rockland; Scituate; Sharon; Stoughton; Taunton; Walpole; West Bridgewater; Westwood; Whitman